Psykisk vold inden for lovens rammer - Mie Mølbak; Caroline Skovgård Jørgensen (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract Psychological violence is a new phenomenon in the Danish criminal justice system. A law against degrading and coercive behavior among close relations was introduced to the Danish Penal Code under § 243 in 2019 to protect victims of this form of violence.